2007
DOI: 10.1161/atvbaha.106.138545
|View full text |Cite
|
Sign up to set email alerts
|

Oxysterol Binding Protein Induces Upregulation of SREBP-1c and Enhances Hepatic Lipogenesis

Abstract: Background-Oxysterol binding protein (OSBP) has previously been implicated as a sterol sensor that regulates sphingomyelin synthesis and the activity of extracellular signal-regulated kinases (ERK). Methods and Results-We determined the effects of adenovirus-mediated hepatic overexpression of OSBP and its homologues ORP1L and ORP3 on mouse serum lipids. Whereas ORP1L and ORP3 had no effect on serum lipids, OSBP induced a marked increase of VLDL triglycerides (TG). Also, the liver tissue TG were elevated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 31 publications
(28 reference statements)
1
61
0
Order By: Relevance
“…The activation of SREBP-1c can cause hepatic lipogenic gene transcription and hepatosteatosis (Jump et al 2005). Increase in the expression of FAS may increase fatty acid synthesis and lead to the ectopic over-accumulation of fatty acids and TG in liver (Yan et al 2007) and the IR (Boden et al 2005). It is known that activated PPARa/g can suppress the expression of SREBP-1, and decrease the synthesis of fatty acids and TG (Konig et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The activation of SREBP-1c can cause hepatic lipogenic gene transcription and hepatosteatosis (Jump et al 2005). Increase in the expression of FAS may increase fatty acid synthesis and lead to the ectopic over-accumulation of fatty acids and TG in liver (Yan et al 2007) and the IR (Boden et al 2005). It is known that activated PPARa/g can suppress the expression of SREBP-1, and decrease the synthesis of fatty acids and TG (Konig et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, oxysterols can bind to the oxysterol binding protein (OSBP)-related proteins (32). OSBP-related proteins constitute a family of cytosolic proteins involved in lipid metabolism (33). Interestingly, recent studies have shown that OSBPs can inhibit the catalytic activity of PP2A phosphatases that are involved in the control of the phosphorylation of Akt (34).…”
Section: Discussionmentioning
confidence: 99%
“…Although several members of the OSBP/ORP family have been putatively associated with some diseases, [37][38][39] the implication in hearing impairment had not been previously reported, and little was known about the relationship between OSBP/ORPs (including other lipid transport proteins) and the cell physiology of the inner ear. Laitinen et al 20 proved that OSBPL2 was expressed in almost all human tissues, but the inner ear or cochlea was not included in that work, and almost nothing was known about the role of OSBPL2 in the human ear.…”
mentioning
confidence: 99%